Kompetensi, Tekanan Anggaran Waktu, dan Kualitas Audit BPK dengan Etika Auditor sebagai Pemoderasi - Pradnyayani, Gusti Ayu Agung Ista; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 33 No 8 (2023)DO - 10.24843/EJA.2023.v33.i08.p15, 2023)
Quality audits from the BPK are needed to ensure accountability and transparency over the use of state finances. This study aims to determine the effect of competence and time budget pressure on BPK audit quality and to determine whether auditor ethics moderates the effect of competence and time budget pressure on BPK audit quality. The research population consisted of 72 BPK RI auditors representing Bali Province with the sample determined using a purposive sampling technique. Variable measurements were carried out using a questionnaire with a 4 point Likert scale. The collected data was analyzed using moderated regression analysis. The results showed that competency had a positive effect on BPK audit quality, time budget pressure had no effect on BPK audit quality, and auditor ethics did not moderate the effect of competence and time budget pressure on BPK audit quality. Keywords: Competence; Time Budget Pressure; Auditor Ethics; Audit Quality